EFEKTIFITAS FRAKSI AKTIF METANOL DAUN SIRIH MERAH (PIPER CROCATUM) YANG BERPOTENSI SEBAGAI ANTIBAKTERI SALMONELLAS TYPHI: (The Effectiveness of Methanol Active Fraction of Red Better Leaves [Piper Crucatum] that Potential as an Antibacterial Salmonellas Typhi) - Mangesa, Rosita; Irsan, Irsan (Uniqbu Journal of Exact Sciences, 2020)
Red betel leaf is a plant that is often used by people as medicine and used as an ornamental plant because of its unique shape. Red betel leaves contain the main essential oil consisting of phenols and their derivatives so that they have potency as an antiseptic and antifungal agent. This study aims to determine the effectiveness of the crude fraction of flavonoid compounds from red betel leaf against Salmonella typhi bacteria and the compound content of the most active fraction. The M1, M2, and M4 fractions contain flavonoid compounds and have the ability to be antibacterial with the best potential fraction is in the M1 fraction with an inhibition zone of 4.83 mm.